Code Switching in Linguistics and its Benefits in Language Teaching - Usmanova Nilufar (International Journal on Human-Computing Studies, 2022)
From a sociolinguistic point of view, the process of switching codes is seen as a means of ethnic self-identification, expression of independence, or as a means of overcoming ethnic barriers. Sociolinguistic studies have shown that it is the characteristics of the communication participants that play the leading role in the choice of the language code. The article deals with the theory of language contacts, bilingualism and code switching and analyzes benefits of code switching in foreign language teaching process.